2016
DOI: 10.1055/s-0036-1582124
|View full text |Cite
|
Sign up to set email alerts
|

Update on Anticoagulation: What the Interventional Radiologist Needs to Know

Abstract: The novel oral anticoagulants (NOACs) represent a major advance in the treatment of patients with nonvalvular atrial fibrillation and venous thromboembolism (VTE). They have several advantages over vitamin-K antagonists such as warfarin, including more predictable pharmacokinetics and improved safety, particularly with fatal bleeding and intracranial hemorrhage. However, several issues remain surrounding the use of NOACs in certain subpopulations and with the approach to reversal. The periprocedural management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…More recent meta-analysis in 2012 showed a major bleed rate on warfarin of 4.7% while a cohort study published in 2016 revealed a combined rate of bleeding with dabigatran or warfarin of 4.6% (9,10). New therapy with DOACs has also improved bleeding rates over warfarin, potentially decreased by half (RR of 0.55) (11). Still, effective treatment for VTE is complicated and in need of additional therapies.…”
Section: Introductionmentioning
confidence: 99%
“…More recent meta-analysis in 2012 showed a major bleed rate on warfarin of 4.7% while a cohort study published in 2016 revealed a combined rate of bleeding with dabigatran or warfarin of 4.6% (9,10). New therapy with DOACs has also improved bleeding rates over warfarin, potentially decreased by half (RR of 0.55) (11). Still, effective treatment for VTE is complicated and in need of additional therapies.…”
Section: Introductionmentioning
confidence: 99%